Pengaruh Produk Minuman Kemasan Asam Jawa (Tamarindus Indica) Terhadap Kekerasan Permukaan Resin Komposit Nanohibrid - Zain, Haura Hafizhah; Harniati, Etny Dyah (Jurnal Material Kedokteran Gigi, 2023)
Composite resin is a frequently used material due to its superior physical and mechanical properties. Nanohybrid composite resin is a newer type of composite resin that incorporates nanotechnology fillers. Surface hardness is a crucial property of composite resin, as it is directly affected by saliva, food, and beverages. This study aimed to determine the effect of packaged tamarind (Tamarindus indica) beverages on the surface hardness of composite resin. This research design was a post-test with control group. Samples were made using a mold with a diameter of 15 mm and a thickness of 2 mm (n=32). Resin komposit yang digunakan adalah Filtek Z50xt shade A3. The samples were divided into 4 groups, distilled water (group I), tamarind drink 2% (group II), 6% (group III), and 15% (group IV), then soaked for 14 minutes in an incubator at 37°C. The samples were tested for surface hardness using a Vickers Hardness Tester. The data analysis used was One Way ANOVA. The average surface hardness value for group I (87.65 ± 7.47 VHN), class II (84.73 ± 3.81 VHN), class III (83.95 ± 4.79 VHN), and class IV (81.85 ± 4.04 VHN). The results of the data analysis showed normal and homogeneous (p>0.05), but the significance value of the parametric test was p=0.194 (p<0.05). Conclusion The nanohybrid composite resin experienced a decrease in hardness after being immersed in tamarind beverage packaging products but this was not significant.